51 Spontaneous coronary artery dissection; a single irish center experience. (6th October 2022) - Gardiner, R; Gill, H; Kiernan, T
Abstract : Introduction: Spontaneous coronary artery dissection (SCAD) is a rare and under-diagnosed cause of acute coronary syndrome (ACS), representing 2–4% of cases. There are no randomised control trials on the subject, therefore management is based on observational studies, case reports and extrapolation of advice from established ACS guidelines. Methods: A search of the McKesson cardiology software identified 13 patients with a SCAD diagnosis on angiogram reports from September 2015 to February 2022. The diagnosis was made on visual inspection of the images by the operator at the time of angiogram ( figure 1 ). Patient data was collected from both electronic records and patient charts. Microsoft Excel was used to generate descriptive statistics of the data. Results: Patient characteristics are demonstrated in table 1 . The majority of patients were male (61.5%), 92.3% had a family history of ACS and 61.5% had a current or past smoking history. Laboratory values, culprit vessel and management are shown in table 2 . The left anterior descending artery was most commonly affected. There was no incidence of multi-vessel SCAD. All patients were treated with aspirin and 92.3% had dual anti-platelet therapy (DAPT), which included one patient also taking an anticoagulant. Ticagrelor was used twice as often as clopidogrel. Two patients (15.4%) had percutaneous coronary intervention (PCI) with drug-eluting stents for ongoing chest pain with dynamic ECG changes. Mean duration of in-hospital stay was 5.8 days. Over half of patients (53.8%) had a re-look angiogram. This was carried out a median of 57 days after the original procedure. There was no incidence of recurrent SCAD in the study period ( figure 2 ). Conclusions: SCAD is infrequently encountered in a single Irish centre. In line with current international practice, PCI is generally avoided, and patients managed with DAPT, beta-blockers, ace-inhibitors and statins. However, there is notable heterogeneity of patient characteristics, risk factor profiles and follow-up. Although patient numbers in this study are small, over half are male. This is in contrast to other studies reporting that females account for approximately 90% of cases. Perhaps cases of SCAD in male patients with more traditional risk factors for ischaemic heart disease are being under-diagnosed, with the cause of ACS being attributed to atherosclerotic plaque rupture. Certainly there is a need for guidelines based on randomised control trials for the management of SCAD, particularly in relation to the use of anti-coagulation and the optimal duration of DAPT.